Multiple Displacement Amplification as a Solution for Low Copy Number Plasmid Sequencing - Yao, Kuan; González-Escalona, Narjol; Hoffmann, Maria (Frontiers in Microbiology, 2021)
Plasmids play a major role in bacterial adaptation to environmental stress and often contribute to antibiotic resistance and disease virulence. Although the complete sequence of each plasmid is essential for studying plasmid biology, most antibiotic resistance and virulence plasmids in Salmonella are present only in a low copy number, making extraction and sequencing difficult. Long read sequencing technologies require higher concentrations of DNA to provide optimal results. To resolve this problem, we assessed the efficiency of multiple displacement amplification for replicating Salmonella plasmid DNA to a satisfactory concentration for accurate sequencing and multiplexing. Nine Salmonella enterica isolates, representing nine different serovars carrying plasmids for which sequence data are already available at NCBI, were cultured and their plasmids isolated using an alkaline lysis extraction protocol. We then used the REPLI-Mini DNA kit to perform multiple displacement amplification, thereby obtaining enough plasmid DNA for long read sequencing. These amplified plasmids were multiplexed and sequenced on one single molecule, real-time (SMRT) Cell with the Pacific Biosciences Sequel sequencer. We were able to close all Salmonella plasmids (sizes ranged from 38 Kb to 166 Kb) with sequencing coverage up to 2000X. This protocol, consisting of plasmid isolation, multiple displacement amplification, and multiplex sequencing, is an effective and fast method for closing high-molecular weight and low-copy-number plasmids. This high throughput protocol reduces the time and cost of plasmid closure.